Lei e história: o poder político, religioso e jurídico da sociedade visigoda no fuero julgo e sua regulamentação fundiária - Lopes, Tallyta Anny Reis Araújo (2018)
It is a research on the Visigothic society in Hispania in 681, especially about its religion, laws and monarchy, making use of Law and History. As for the royal power and the Visigothic Catholic religion, they had an intimate connection. The study seeks to analyze not only the Visigothic law of the year 681 made in Hispania during the reign of Sisenando but also to relate it to the historiography and to the legal and political power of the Visigoths. The choice of this topic was by affinity and the methodology used was the analysis of the Fuero Juzgo, a law elaborated in 681 during the Fourth Council of Toledo, being that diversity marks the Iberian world and the bishops possessed great power and prestige in the Spanish- visigoda, legitimating the kings. In the end, a virtual learning object, an exe file with the contents studied in a simpler language and summarized for high school students, was carried out in order to disseminate this work.